The Architecture of the Ancient Greek Theatre - Sokolicek, Alexander; Gebhard, Elizabeth R.; Frederiksen, Rune (Book collections on Project MUSE., 2015)
In this volume the leading experts on ancient Greek theatre architecture present new excavation results and new analyses of individual monuments. Many well-known theatres such as the one of Dionysos in Athens and others at, for instance, Messene, Sikyon, Chaironeia in Greece and Aphrodisias in Turkey, have been re-examined since their original publication with stunning results. New research also includes less well-known or newly discovered ancient Greek theatres in Albania, Turkey, Cyprus and Sicily. Further studies on the history of research, regional theatrical developments, terminology and function, as well as a perspective on Roman theatres built in Greek traditions make this volume a comprehensive book of new research for specialist scholars as well as for students and the interested public. Fundamental publications on the topic have not been presented for many years, and this book aims to form a new foundation for the study of theatre architecture.